Experimental investigation and life-cycle cost analysis of a cold storage enhanced vacuum cooling system using ice slurry. (June 2021) - Zhang, Chong; Yang, Luwei; Lin, Wenye; Wei, Juan; Chen, Jiaxiang; Ma, Zhenjun
Highlights: A cold storage enhanced vacuum cooling (CSVC) system using ice slurry was developed. Using cold storage reduced the initial and operation cost of vacuum cooling systems. Life-cycle cost of the CSVC was 71.1% of a conventional vacuum cooling system. A low volume pumping rate increased energy consumption and operation cost of CSVC. Abstract: This paper presents the development, experimental investigation, and life-cycle cost analysis of a novel cold storage enhanced vacuum cooling (CSVC) system using ice slurry. Compared to a conventional direct vacuum cooling (DVC) system, the proposed system featured the integration of a cold storage section to temporarily store the ice slurry generated during off-peak electricity demand period, which was then utilised to facilitate the vacuum cooling over the peak demand period. It was found from the comparative experimental study that the CSVC system using ice slurry can effectively provide similar vacuum cooling effect as the DVC system on the pre-cooling process of lettuces. The life-cycle cost analysis demonstrated that the net present operation cost of the CSVC system over a life-cycle period of 10 years was 30.2% lower than that of the DVC system, although its energy consumption was 28.1% higher. The employment of cold storage also significantly cut down the size of the refrigeration unit, which contributed to reducing the initial investment. The total life-cycle cost of the CSVC system was 10, 393, which was only 71.1% of the DVC system. Also, reducing the volume pumping rate in the CSVC system did not affect the weight loss of the pre-cooled products.